Form expression of "Kelenteng Hok Tek Bio" Chinese temple related to the function, building structure, and symbol. Issue 1 (31st December 2023) - Trisno, Rudy; Lianto, Fermanto
Abstract: The design of the kelenteng (temple) building using a typology of the form of the Chinese temple building is very interesting to be used as a research issue, which raises some interesting questions, namely: (1) Does this aim at the uniformity of all the temples outside China?; (2) Is this building still feasible to use wooden structures?; (3) What about the "sign" meaning of the symbol?. This study aims to find information on how the "Kelenteng Hok Tek Bio " (Chinese temple) in anticipating this problem with the development of people who tended to increase after the fall of the New Order government in 1998 Chinese religious rituals permitted again. The method is qualitative interpretative research. The conclusion obtained in this study is; (1) The "Kelenteng Hok Tek Bio " has Si He Yuan courtyard type in the middle of the building with a symmetrical form. It looks like a Chinese Temple; (2) The structure used is wood and concrete adapted to the spirit of the age; (3) The "sign" meaning is index, symbol, and icon. The findings are "function follows the form", and the kelenteng has a courtyard, symmetrical form, wooden and concrete structures, the "sign" meaning of the building can be an index for Feng Shui, symbols for ornamentation, and icon for flora, fauna, even the hànzì script.